Label-free quantitative proteomics of arbuscular mycorrhizal Elaeagnus angustifolia seedlings provides insights into salt-stress tolerance mechanisms - Chang, Wei; Zhang, Yan; Ping, Yuan; Li, Kun; Qi, Dan-Dan; Song, Fu-Qiang (Frontiers in Plant Science, 2023)
Introduction Soil salinization has become one of the most serious environmental issues globally. Excessive accumulation of soluble salts will adversely affect the survival, growth, and reproduction of plants. Elaeagnus angustifolia L., commonly known as oleaster or Russian olive, has the characteristics of tolerance to drought and salt. Arbuscular mycorrhizal (AM) fungi are considered to be bio-ameliorator of saline soils that can enhance the salt tolerance of the host plants. However, there is little information on the root proteomics of AM plants under salt stress. Methods In this study, a label-free quantitative proteomics method was employed to identify the differentially abundant proteins in AM E. angustifolia seedlings under salt stress. Results The results showed that a total of 170 proteins were significantly differentially regulated in E.angustifolia seedlings after AMF inoculation under salt stress. Mycorrhizal symbiosis helps the host plant E. angustifolia to respond positively to salt stress and enhances its salt tolerance by regulating the activities of some key proteins related to amino acid metabolism, lipid metabolism, and glutathione metabolism in root tissues. Conclusion Aspartate aminotransferase, dehydratase-enolase-phosphatase 1 (DEP1), phospholipases D, diacylglycerol kinase, glycerol-3-phosphate O-acyltransferases, and gamma-glutamyl transpeptidases may play important roles in mitigating the detrimental effect of salt stress on mycorrhizal E. angustifolia . In conclusion, these findings provide new insights into the salt-stress tolerance mechanisms of AM E. angustifolia seedlings and also clarify the role of AM fungi in the molecular regulation network of E. angustifolia under salt stress.